2003
DOI: 10.1007/s11906-003-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of RhoA and Rho-associated kinase in vascular smooth muscle contraction

Abstract: A variety of contractile agonists trigger activation of the small GTPase RhoA. An important target of activated RhoA in smooth muscle is Rho-associated kinase (ROK), one of the downstream targets that is the myosin binding subunit (MYPT1) of myosin light chain phosphatase (MLCP). Phosphorylation of MYPT1 at T695 by activated ROK results in a decrease in phosphatase activity of MLCP and an increase in myosin light chain (LC(20)) phosphorylation catalyzed by Ca(2)(+)/calmodulin-dependent myosin light chain kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 46 publications
5
120
0
2
Order By: Relevance
“…It has been reported that this pyridine derivative is ϳ200 -2,000 times more specific for Rho kinase than other protein kinases including Ca 2ϩ -dependent PKC, MLC kinase, and cAMP-dependent protein kinase that are the major players in regulation of smooth muscle tone (7,16,42). Sakamoto et al (30) demonstrated that Y-27632 has no direct effects on intracellular Ca 2ϩ levels or the activities of MLC phosphatase and MLC kinase at concentrations Ͻ100 M. Studies using Y-27632 have shown Rho kinase to mediate the tonic component of vasoconstrictor responses to agonists including PE, serotonin, ET-1, prostaglandin F 2␣ , and histamine (39,40). In this study, we demonstrate that 1 M Y-27632 abolishes X/XO-induced contractions but not PDBu-induced contractions, suggesting a role for Rho kinase as a mediator of the X/XO-induced contractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this pyridine derivative is ϳ200 -2,000 times more specific for Rho kinase than other protein kinases including Ca 2ϩ -dependent PKC, MLC kinase, and cAMP-dependent protein kinase that are the major players in regulation of smooth muscle tone (7,16,42). Sakamoto et al (30) demonstrated that Y-27632 has no direct effects on intracellular Ca 2ϩ levels or the activities of MLC phosphatase and MLC kinase at concentrations Ͻ100 M. Studies using Y-27632 have shown Rho kinase to mediate the tonic component of vasoconstrictor responses to agonists including PE, serotonin, ET-1, prostaglandin F 2␣ , and histamine (39,40). In this study, we demonstrate that 1 M Y-27632 abolishes X/XO-induced contractions but not PDBu-induced contractions, suggesting a role for Rho kinase as a mediator of the X/XO-induced contractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, suppresses stress fiber formation and dramatically augments hypertension in rat models (28). There are numerous other pivotal actin-associated effectors that are downstream of Rho GTPase signaling, including myristolated alanine-rich C kinase substrate (MARCKS), the LIM kinases, and their downstream phosphoeffector capable of promoting actin filament disassembly, cofilin (11,26). These observable pathways that converge on actinbased cytoskeletal remodeling represent a limited molecular understanding of Rho GTPase function and cytoskeletal signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…20 Phosphorylation and inhibition of small GTPase RhoA will inhibit Rho kinase which, in turn, dephosphorylates the MYPT1 and then increases the myosin light chain phosphatases activity. [20][21][22] rHBD2 inhibited MLC 20 and MYPT1 phosphorylation and increased RhoA phosphorylation (Figure 1B-1D). These results suggest that rHBD2 dephosphorylates MLC 20 and MYPT1 by inhibiting RhoA and, thus, relaxes smooth muscle and lowers blood pressure.…”
Section: Discussionmentioning
confidence: 90%